Estimation of Photovoltaic Panel Parameters by a Numerical Heuristic Searching Algorithm - Mesbahi, Oumaima (2020)
This work uses the Nelder-Mead approach, which is a direct search optimization method, to obtain the accurate photovoltaic parameters by minimizing a predetermined objective function of five variables. This paper presents some new modifications made to the Nelder-Mead algorithm which allow a better convergence of the method. A comparison study has conducted between this proposed technique and a classical Nelder-Mead algorithm towards the additive noise of the current along with a sensitivity analysis towards the resolution of ADC.